MEDICAL EDUCATOR’S NONVERBAL BEHAVIOR AND ITS IMPACT ON STUDENTS AND EDUCATIONAL ENVIRONMENT - Aziz, Anbreen; Majeed, Farzana; Saadia Muneer Malik (Journal of University Medical & Dental College, 2021)
BACKGROUND & OBJECTIVE: Nonverbal communication has been overlooked in medical education. The purpose of this study was to explore student-teacher perceptions regarding impact of nonverbal behavior of medical educators on educational environment. METHODOLOGY: A qualitative exploratory study was conducted among purposively chosen final year students (n=150) and medical teachers (n=73) from three dental colleges of Islamabad. A web-based survey concerning three domains of kinesics (Facial expressions, Gestures, Head movement and postures) was developed and validated before execution. Comparison of participant’s responses to closed-ended questions was done by applying Fisher’s Exact Test and open-ended questions were thematically analyzed. RESULTS: Response rate of students and teachers was 46% and 63% respectively. Five out of nine closed-ended questions gave statistically significant difference among student’s and teacher’s responses (p≤0.05). Twenty-seven subthemes emerged from three domains of kinesics. Students revealed that happy mood of their teachers reduces boredom in the classroom and a teacher’s smile lets them freely express anything, whereas anger produces fear among them. According to the educators a happy instructor inspires students to study and makes the environment friendly and an undemanding smile helps build a rapport with students. Moreover, positive gestures used by teachers encourage students to clarify concepts and upright posture brings energy and motivation to the classroom. CONCLUSION: A teacher’s nonverbal behavior has a profound effect on educational environment. A smile on a teacher’s face creates a friendly and fearless environment whereas anger creates barriers to communication. A happy teacher can generate a pleasant and motivating learning environment.